Effectiveness of Chewing Gum Therapy as Prevention of Post-Operative Ileus (POI) in Post-Laparotomy Surgery Patients in the Mawar Room of RSD dr. Soebandi Jember - Naili, Naila Khoirun; Hakam, Mulia; Siswoyo; Shodikin, Mohammad (Jurnal Kesehatan Komunitas Indonesia, 2025)
Background: Post-operative ileus or POI is one of the most common problems found and disruptive after laparotomy or laparoscopy, both electively and emergency. Potential complications that can arise from POI with a prolonged period include increased post-operative pain, increased nausea and vomiting, complications in the lungs, worsening of the surgical wound healing process, inadequate oral intake, delayed post-operative mobilization, a long hospitalization period, and increased healthcare costs. Therefore, a non-pharmacological approach is needed to minimize the incidence of POI, including chewing gum therapy. Purpose: To determine the effectiveness of chewing gum therapy in preventing Post-Operative Ileus (POI) in post-laparotomy patients. Method: A case study involving two patients: intervention patients and comparison patients. Chewing gum therapy is given as much as two pieces with a chewing time of 10-15 minutes in a total of 3 times/day, and observations are carried out every 6 hours. Results: The average pain scale was lower in intervention patients, nausea occurred in comparison patients, the average bowel sounds were higher in intervention patients, and the time to the first fart after surgery was shorter in intervention patients compared to comparison patients. Conclusion: Chewing gum therapy can reduce symptoms of POI complications and accelerate the reactivation of gastrointestinal motility after surgery.